The Adjuvant Bordetella Colonization Factor A Attenuates Alum-Induced Th2 Responses and Enhances Bordetella pertussis Clearance from Mouse Lungs - Jennings-Gee, Jamie (Infect Immun, 2018)
The reemergence of pertussis or whooping cough in several countries highlights the need for better vaccines. Acellular pertussis vaccines (aPV) contain alum as the adjuvant and elicit Th2-biased immune responses that are less effective in protecting against infection than the reactogenic whole-cell pertussis vaccines (wPV), which elicit primarily a Th1/Th17 response. An important goal for the field is to devise aPV that will induce immune responses similar to those of wPV. We show that Bordetella colonization factor A (BcfA), an outer membrane protein from Bordetella bronchiseptica, has strong adjuvant function and elicits cellular and humoral immune responses to heterologous and Bordetella pertussis antigens. Addition of BcfA to a commercial aPV resulted in greater reduction of B. pertussis numbers from the lungs than that elicited by aPV alone. The more-efficient pathogen clearance was accompanied by increased interleukin-17 (IL-17) and reduced IL-5 and an increased ratio of IgG2/IgG1 antibodies. Thus, our results suggest that BcfA improves aPV-induced responses by modifying the alum-induced Th2-biased aPV response toward Th1/Th17. A redesigned aPV containing BcfA may allow better control of pertussis reemergence by reshaping immune responses to resemble those elicited by wPV immunization.